APPLICATION OF PRIGOGINE-FLORY-PATTERSON THEORY TO EXCESS MOLAR VOLUMES OF BINARY LIQUID MIXTURES OF {METHYL TERT BUTYL ETHER (MTBE) + ALCOHOLS} AT DIFFERENT TEMPERATURES AND ATMOSPHERIC PRESSURE - Hoga, Heloisa Emi (2018)
In the present study, experimental data of excess molar volumes ( ) of binary liquid mixtures of methyl tert butyl ether (MTBE) + methanol, or + ethanol, or + 1-propanol, or + 2-propanol, or + 1-butanol, or + 1-pentanol, or + 1-hexanol have been used to test the applicability of the Prigogine-Flory-Patterson theory (PFP) as a function of composition at different temperatures and atmospheric pressure. According to the model, interactional contribution is the most important one to explain the behavior. It may be observed that the PFP theory reproduces the main features of the experimental data by using only one fitted parameter adjusted. Good agreements between the experimental results and the theory were obtained for all the systems studied.